The moderating effect of delay discounting between sensation seeking and risky driving behavior. (March 2020) - Qu, Weina; Zhang, Weibin; Ge, Yan
Highlights: Delay discounting did not significantly positively predict risky driving behavior. Sensation seeking in concert with delay discounting led to risky driving behavior. Sensation seeking predicted risky behavior for drivers with a high discounting rate. Sensation seeking had no effect for drivers with a low discounting rate. Abstract: Delay discounting refers to the perceived value of a reward decreasing as the delay of the reward increases, which represents an individual's tendency to choose immediate monetary rewards or larger delayed rewards. It has been found that sensation seeking is a robust predictor of risky driving behavior, such as violations. Given that risky driving behavior may be associated with a tradeoff between immediate sensation satisfaction and delayed safety benefits, the aim of the present study was to investigate the relationship between people's delay discounting rate with hypothetical monetary rewards and their self-reported risky driving behaviors as well as explore the possible moderating effect of delay discounting on the relationship between sensation seeking and risky driving. A total of 329 Chinese drivers completed Zuckerman's Sensation Seeking Scale, the Monetary Choice Questionnaire and the Driver Behavior Questionnaire. The results did not reveal a significant and positive correlation between delay discounting and risky driving behavior. Instead, we found that the discounting rates with a large magnitude of delayed money could negatively predict ordinary violations, errors and total risky driving behaviors. Meanwhile, the delay discounting rate moderated the relationship between sensation seeking and risky driving. Specifically, sensation seeking had an influence on risky driving behavior only in drivers with a high discounting rate and not in drivers with a low discounting rate. This study was the first to examine the simultaneous influence of sensation seeking and delay discounting on risky driving. This study enriched the current theoretical framework and could be applied to selecting and training drivers and improving road safety.